Anatomical Applicability of Endovascular Aneurysm Sealing Techniques in a Consecutive Cohort of Fenestrated Endovascular Aneurysm Repairs. (December 2017) - Roy, Iain N.; Gharib, Menatalla; Zerwes, Sebastian; Jakob, Rudolf; Torella, Francesco; McWilliams, Richard G.; Fisher, Robert K.
Purpose: To determine how many endovascular aneurysm sealing (EVAS) procedures with/without off-label use of chimneys (ChEVAS) could have been performed in a cohort of patients who had undergone fenestrated endovascular aneurysm repair (FEVAR).Methods: Sixty patients (median age 76.3 years; 54 men) who underwent FEVAR in our institution between 2013 and 2015 were selected for the study. The median aneurysm diameter was 62.0 mm (interquartile range 59.3, 69.0). Preoperative computed tomography angiograms (CTA) were anonymized and sent to 2 physicians with experience of more than 40 ChEVAS interventions. These ChEVAS planners were blinded to the study purpose and asked to agree upon an EVAS/ChEVAS plan. The primary outcome was the percentage of the FEVAR patients in whom an EVAS/ChEVAS was technically possible. The secondary outcomes were a comparison of seal zones, number of target vessels, and device cost.Results: An EVAS-based intervention would have been technically possible in 56 (93.3%) of the FEVAR patients. The median proximal aortic seal zone was significantly more distal in the EVAS/ChEVAS procedures vs the FEVAR cases (zone 8 vs zone 7, p<0.001) and fewer target vessels were involved (median 2 vs 3, p<0.001). The cost of the EVAS/ChEVAS device was 66% of the FEVAR device. Planners would not currently advocate an EVAS-based intervention in 43 (76.8%) of these 56 patients due to concerns regarding the risk of migration associated with the lumen thrombus ratios observed.Conclusion: EVAS is technically feasible in the majority of patients undergoing FEVAR in our institution but currently advocated in only 23.2%. The seal zone was more distal, fewer target vessels were involved, and the device cost was lower in the planned EVAS/ChEVAS interventions.